2018
DOI: 10.1056/nejmoa1716026
|View full text |Cite
|
Sign up to set email alerts
|

Radial-Artery or Saphenous-Vein Grafts in Coronary-Artery Bypass Surgery

Abstract: As compared with the use of saphenous-vein grafts, the use of radial-artery grafts for CABG resulted in a lower rate of adverse cardiac events and a higher rate of patency at 5 years of follow-up. (Funded by Weill Cornell Medicine and others.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
283
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 450 publications
(295 citation statements)
references
References 20 publications
6
283
0
6
Order By: Relevance
“…481 A recently published patient-level meta-analysis pooling six RCTs comparing radial artery vs. saphenous vein graft showed that the use of the radial artery was associated with a lower rate of the primary endpoint (composite of death, myocardial infarction, and repeat revascularization) at mean follow-up of 50 months, mainly driven by a significantly strong reduction of need for reintervention and a more modest reduction in subsequent MI. 482 Despite a significantly lower risk of occlusion at follow-up angiography, no difference in all-cause mortality was found.…”
Section: Conduit Selectionmentioning
confidence: 90%
“…481 A recently published patient-level meta-analysis pooling six RCTs comparing radial artery vs. saphenous vein graft showed that the use of the radial artery was associated with a lower rate of the primary endpoint (composite of death, myocardial infarction, and repeat revascularization) at mean follow-up of 50 months, mainly driven by a significantly strong reduction of need for reintervention and a more modest reduction in subsequent MI. 482 Despite a significantly lower risk of occlusion at follow-up angiography, no difference in all-cause mortality was found.…”
Section: Conduit Selectionmentioning
confidence: 90%
“…12 The results of our study are almost identical to our very recently published meta-analysis of randomized controlled trials comparing RA versus SVG performance for CABG. 22 In this study with comparable numbers of conduits, the incidence of adverse cardiac events was significantly lower in association with RA grafts. Moreover again, the use of RA was associated with lower risk for repeat revascularization at 5 years' follow-up.…”
Section: Discussionmentioning
confidence: 51%
“…Here, the authors refer to the RADIAL Investigator trial, where at a mean follow-up of 5 years the radial artery was associated with a significantly lower risk of adverse cardiac events, repeat revascularization, and myocardial infarction and a better patency rate compared with the saphenous vein. 3 It is noteworthy that, in the majority of trials in their analysis, the saphenous veins were harvested with pedicle removed as originally described by Favaloro, 2 whereas the radial arteries were harvested with pedicle intact. An atraumatic, no-touch, technique of harvesting the saphenous vein provides an improved graft with a long-term patency comparable with the internal thoracic artery at 16 years.…”
Section: Arterial Versus Venous Conduits In Coronary Artery Bypass Sumentioning
confidence: 99%
“…2 Supporting their claim on the RADIAL fruit salad, Dashwood and Loesch quote a small randomized trial by Dreifaldt and colleagues 3 that shows a better patency rate for the no-touch saphenous vein than for the radial artery, and an aggregate data meta-analysis of the trials included in RADIAL, with the addition of the latter study reporting the same result. 4 As detailed elsewhere, the study of Dreifaldt and colleagues 3 was not included in the RADIAL analysis after a careful evaluation of its several methodologic flaws. 5 The most important (and fatal) flaw was its unique use of the radial artery in open contrast with all the guidelines and recommendations (and the common practice), which require target vessel stenosis to be less than 70% in the left coronary system and 90% in the right.…”
Section: Arterial Versus Venous Conduits In Coronary Artery Bypass Sumentioning
confidence: 99%